2009
DOI: 10.1158/1055-9965.epi-07-2558
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Psychosocial Factors Influencing Colorectal Cancer Patients' Communication of Colorectal Cancer Patient Risk with Their Siblings

Abstract: This study examined psychosocial factors influencing colorectal cancer (CRC) patients' communication with their first-degree relatives regarding their CRC risk. Among a sample of CRC patients who were members of a colon registry in New York (n = 127), 60% reported discussing CRC risk with their siblings. These discussions were related to the CRC patients' age of diagnosis, such that those diagnosed before age 45 years were more likely to communicate with their siblings about CRC risk. Despite advances made in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…We found that a higher percentage of CRC patients were informed of their FDRs' increased CRC risk (80.6%) than in other studies (33-77.6%) [3,5,8,[19][20][21][22][23] Several factors might have influenced the high rate of informed CRC patients in our study. First, the flow of information is better in young index patients with CRC and in conditions with strong family togetherness [3,24,25]. The mode of questionnaire distribution in our study implied strong togetherness within the affected families because the FDRs' consent had to be obtained by the CRC patients (selectional bias).…”
Section: Discussionmentioning
confidence: 78%
“…We found that a higher percentage of CRC patients were informed of their FDRs' increased CRC risk (80.6%) than in other studies (33-77.6%) [3,5,8,[19][20][21][22][23] Several factors might have influenced the high rate of informed CRC patients in our study. First, the flow of information is better in young index patients with CRC and in conditions with strong family togetherness [3,24,25]. The mode of questionnaire distribution in our study implied strong togetherness within the affected families because the FDRs' consent had to be obtained by the CRC patients (selectional bias).…”
Section: Discussionmentioning
confidence: 78%
“…To date, much of the literature on family history discussions about cancer have focused on patient-physician communication (Smith et al, 2011; Dickerson et al, 2012; Bell et al, 2015), communication among relatives of cancer survivors (Harris et al, 2010; Hay et al, 2009; Lawsin et al, 2009), and discussions surrounding genetic test results (Aktan-Collan et al, 2011; Bradbury et al, 2012; McCann, et al, 2009; Vos et al, 2011). Fewer studies have sought to identify family context or individual factors that may promote family health history discussions, yet this type of information could be used to identify families who may need support in having these conversations.…”
Section: Discussionmentioning
confidence: 99%
“…These aspects, as well as the content and consequences of this family communication, would deserve to be explored further in other studies. Finally, although we did not assess this, life events, and particularly cancer-related life events, may also contribute to initiate discussions about cancer risk in families without a member tested for BRCA1/2 (Hay et al 2005;Hay et al 2008;Lawsin et al 2009;Pho et al 2000;Schroy et al 2005). Communication about cancer risk is, however, particularly relevant in families who are at high risk for cancer and, even more, when one of its members had the opportunity to receive detailed information about the impact of familial susceptibility through genetic counseling services.…”
Section: Study Limitationsmentioning
confidence: 99%